Aplicativo Android para envio de movimentos sequenciais a um braço robótico educacional por comunicação Bluetooth - Souza, João Igor Carneiro de (2025)
This paper presents the development of a mobile application for controlling an educational robotic arm via Bluetooth communication, using Android devices. The growing demand for technological tools in education justifies the creation of an interactive solution, allowing students to manipulate the equipment in real time, promoting hands-on learning in subjects such as robo- tics, automation, and programming. The application was developed based on the React Native framework, enabling an intuitive interface compatible with most mobile devices. Communication between the application and the robotic arm occurs through a Bluetooth module integrated with an Arduino, which interprets and executes commands sent by the user. The project was structured following the Scrum methodology, allowing for iterative and incremental development, with continuous testing and validation cycles. The results demonstrate that the developed application provides precise and efficient control of the robotic arm, with good responsiveness and usability. The presented solution contributes to the integration of robotics into the educational environment, making learning more dynamic and accessible. Improvements may be implemented in the future, such as new features and expanded compatibility with other platforms.